SiO2 Template-assisted Synthesis of CdS Hollow Nanospheres With Enhanced Photocatalytic Properties - Wang, Junyi; Ji, Guangbin; Liu, Yousong; Chang, Xiaofeng (Current Nanoscience, 2013)
CdS hollow nanospheres with enhanced photocatalytic performance have been prepared by employing SiO2 nanospheres as templates with a simple and mild solution reaction at room temperature. Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) analyses confirmed that these CdS hollow nanospheres possess 370 nm diameter and the wall thickness less than about 30 nm. UV-Vis absorption spectra show that the as-synthesized hollow CdS nanospheres display better light absorption ability than the contracted solid CdS nanospheres. Furthermore, the hollow CdS nanospheres exhibit enhanced activity toward decomposition of target organic pollutant such as Rhodamine B (RhB), under Xe arc lamp irradiation. The calculated rate constants for hollow CdS nanospheres are 5.5 times larger than that of solid CdS nanospheres, which could be ascribed to the improved light absorption ability, adsorption capability due to the hollow structure, and higher charge separation efficiency achieved by shortening the charge transporting path with thinner hollow CdS shell.
Keywords: clean water and clean energy